In Vitro Adsorption of Analgosedative Drugs in New Extracorporeal Membrane Oxygenation Circuits. Issue 5 (May 2018) - Raffaeli, Genny; Allegaert, Karel; Koch, Birgit; Cavallaro, Giacomo; Mosca, Fabio; Tibboel, Dick; Wildschut, Enno D.
Abstract : Objective: Evaluate drug disposition of sedatives and analgesics in the Xenios/Novalung extracorporeal membrane oxygenation circuits. Design: In vitro experimental study. Setting: Erasmus MC - Sophia Children's Hospital, Rotterdam, The Netherlands. Subjects: Nine closed-loop extracorporeal membrane oxygenation circuits, made up of the iLA Activve console with four different iLA Activve kits : two X-lung kits, two iLA-Activve iLA kits, two MiniLung kits, and three MiniLung petite kits. Interventions: The circuits were primed with fresh whole blood and maintained under physiologic conditions (pH/temperature) throughout 24 hours. Paracetamol, morphine, midazolam, fentanyl, and sufentanil were injected as standard age-related doses into nine closed-loop extracorporeal membrane oxygenation circuits. Measurements and Main Results: Pre-membrane (P2) blood samples were obtained prior to drug injection and after injection at 2, 10, 30, 180, 360 minutes, and at 24 hours. A control sample at 2 minutes was collected for spontaneous drug degradation testing at 24 hours. Two hundred sixteen samples were analyzed. After correction for the spontaneous drug degradation, the mean drug loss at 24 hours was paracetamol 49%, morphine 51%, midazolam 40%, fentanyl 84%, sufentanil 83%. Spontaneous degradation was paracetamol 6%, morphine 0%, midazolam 11%, fentanyl 4%, and sufentanil 0%. The decline of drug concentration over time was more pronounced for the more lipophilic drugs. Conclusions: Loss of highly lipophilic drugs in the extracorporeal membrane oxygenation circuits at 24 hours was remarkable. Drug loss is comparable with other hollow fiber extracorporeal membrane oxygenation systems but less than in silicone-based membranes especially in the first hours after injection.